Intralesional traction‐assisted endoscopic submucosal dissection for early gastric neoplasm using the ProdiGI traction wire. Issue 3 (16th February 2022) - Shoguchi, Yoshihisa; Esaki, Mitsuru; Minoda, Yosuke
Abstract : Watch a video of this article